Analisis Pelaksanaan Strategi Perbankan Dalam Menghadapi Kejahatan Fraud Kartu Kredit Di BCA KCP Kota Baru Parahyangan - Trisiani, Rini; Muhiban, Ayi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Credit card crimes, including fraud and data misuse, have become a major challenge for banking and financial institutions. The purpose of this study is to analyze the implementation of banking strategies in addressing credit card fraud at BCA KCP Kota Baru Parahyangan. The research method used is descriptive qualitative. The findings show that BCA KCP Kota Baru Parahyangan has implemented various strategies, including the use of EMV (Euro, Mastercard, Visa) chips, OTP (One Time Password), machine learning–based transaction monitoring systems, layered verification procedures, regular internal audits, and customer education through the #AwasModus campaign. In addition, strategies are strengthened by employee training, inter-unit coordination, and cooperation with law enforcement agencies. These strategies demonstrate a strong commitment to integrating technology, human resources, and regulatory aspects in combating fraud threats. The conclusion and recommendations suggest that preventing credit card fraud requires simple digital education for the public, additional supervisory personnel, and staff rotation. The bank should optimize AI, Big Data, and surprise audits for early detection. Branch–head office coordination should be enhanced with case study–based training. Furthermore, a real-time alert system for customers is crucial to accelerate responses to suspicious transactions.